Comprehensive Review of Nursing Practices in Emergency Care, Chronic Disease Management, And Mental Health - Alsuwat, Abdulrahman Abdullah; Althobaiti, Faisal Khalid; Almutairi, Qaed Mohammed; Algethami, Osama Awadh; Alqarni, Abdulaziz Ali; Alahmari, Rakan Ali; Al-Qarni, Asmaa Hamoud; Alswat, Muruj Sultan; Almalki, Emad Hussain; Al-Thobaiti, Mansour Abdulmalik (Journal of Ecohumanism, 2024)
Emergency nursing and nursing of chronic diseases and patients with mental illnesses are critical aspects of today’s healthcare systems. Nurses have a central responsibility to fulfill the healing outcomes across all these realms of practice, where professional knowledge and the art of healing can touch literally and figuratively and transform a patient’s life. This review provides a focused analysis of changes and impacts of nursing care in these three essential features, challenges, creative solutions, and evidence-based developments of nursing care for emergency departments, chronic disease clinics, and mental health care facilities. Drawing from current developments in technology and practice, this paper gives a clear and impressive picture of how nurses manage acute and chronic diseases. In addition, the review encompasses recommendations on the need to promote and implement the best practices to address the challenges relating to nursing in those critical care fields.